Manipulation Tests in Regression Discontinuity Design: The Need for Equivalence Testing - Jack Fitzgerald (Institute for Replication (I4R), 2024)
Researchers utilizing regression discontinuity design (RDD) commonly test for running variable (RV) manipulation around a cutoff, but incorrectly assert that insignificant manipulation test statistics are evidence of negligible manipulation. I introduce simple frequentist equivalence testing procedures that can provide statistically significant evidence that RV manipulation around a cutoff is practically equal to zero. I then demonstrate the necessity of these procedures, leveraging replication data from 36 RDD publications to conduct 45 equivalence-based RV manipulation tests. Over 44% of RV density discontinuities at the cutoff cannot be significantly bounded beneath a 50% upward jump. Bounding equivalence-based manipulation test failure rates beneath 5% requires arguing that a 350% upward density jump is practically equal to zero. Meta-analytic estimates reveal that average RV manipulation around the cutoff is equivalent to a 26% upward density jump. These results imply that many published RDD estimates may be confounded by discontinuities in potential outcomes due to RV manipulation that remains undetectable by existing tests. I provide research guidelines and commands in Stata and R to help researchers conduct more credible equivalencebased manipulation testing in future RDD research.
Keywords: C12; C18; C87; P00; 330; McCrary density test; rddensity; DCdensity; Hartman test